Characteristics of Being a "Good Professional" in the Opinion of Mexican College Students - Edna Luna Serrano; María del Consuelo Valle Espinosa; Cecilia Osuna-Lever (Universidad Autónoma de Baja California, 2010)
The purpose of this study was to identify and define a hierarchical organization of the most significant traits of being a good professional derived from the opinions of students of a public university. In a descriptive study a sample of 2756 students represented six knowledge areas was successively surveyed. Quantitative and qualitative analyses were used. The contrast of the general hierarchical organization from the point of view of knowledge areas and the curricular stage confirmed that the most valued traits were responsibility, honesty and knowledge. The least important were team work and communication. Opinion coincidence was identified between knowledge area and curricular stage opinions regarding the most and least important traits. No differences were found between freshmen and senior college students' preferences. The results seem to favor an explicit incorporation of professional value formation in students.